Prevalence of Hypertension, Obesity, Diabetes, and Metabolic Syndrome in Nepal - Sanjib Kumar Sharma; Anup Ghimire; Jeyasundar Radhakrishnan; Lekhjung Thapa; Nikesh Raj Shrestha; Navaraj Paudel; Keshar Gurung; Maskey R; Anjali Budathoki; Nirmal Baral; David Brodie (International Journal of Hypertension)
Background. This study was carried out to establish the prevalence of cardiovascular risks such as hypertension, obesity, and diabetes in Eastern Nepal. This study also establishes the prevalence of metabolic syndrome (MS) and its relationships to these cardiovascular risk factors and lifestyle. Methods. 14,425 subjects aged 20–100 (mean 41.4 ± 15.1) were screened with a physical examination and blood tests. Both the International Diabetic Federation (IDF) and National Cholesterol Education Programme’s (NCEP) definitions for MS were used and compared. Results. 34% of the participants had hypertension, and 6.3% were diabetic. 28% were overweight, and 32% were obese. 22.5% of the participants had metabolic syndrome based on IDF criteria and 20.7% according to the NCEP definition. Prevalence was higher in the less educated, people working at home, and females. There was no significant correlation between the participants’ lifestyle factors and the prevalence of MS. Conclusion. The high incidence of dyslipidemia and abdominal obesity could be the major contributors to MS in Nepal. Education also appears to be related to the prevalence of MS. This study confirms the need to initiate appropriate treatment options for a condition which is highly prevalent in Eastern Nepal.